Adaptations of placental and cord blood ABCA1 DNA methylation profile to maternal metabolic status - Houde, Andrée-Anne (Landes Bioscience, 2013)
In utero environmental perturbations have been associated with epigenetic changes in the offspring and a lifelong susceptibility to cardiovascular diseases (CVD). DNA methylation at the ATP-binding cassette transporter A1 (ABCA1) gene was previously associated with CVD, but whether these epigenetic marks respond to changes in the maternal environment is unknown. This study was undertaken to assess the associations between the maternal metabolic profile and ABCA1 DNA methylation levels in placenta and cord blood. Placenta and cord blood samples were obtained at delivery from 100 women including 26 with impaired glucose tolerance (IGT) diagnosed following a 75 g-oral glucose tolerance test (OGTT) between week 24 and 28 of gestation. ABCA1 DNA methylation and mRNA levels were measured using bisulfite pyrosequencing and quantitative real-time PCR, respectively. We report that ABCA1 DNA methylation levels on the maternal side of the placenta are correlated with maternal high density lipoprotein cholesterol (HDL-C) levels (r < –0.21; P < 0.04) and glucose levels 2 h post-OGTT (r = 0.25; P = 0.02). On the fetal side of the placenta, ABCA1 DNA methylation levels are associated with cord blood triglyceride levels (r = –0.28; P = 0.01). ABCA1 DNA methylation variability on both sides of the placenta are also associated with ABCA1 mRNA levels (r < –0.35; P = 0.05). As opposed to placenta, cord blood DNA methylation levels are negatively correlated with maternal glucose 2 h post-OGTT (r = –0.26; P = 0.02). In conclusion, the epivariations observed in placenta and cord blood likely contribute to an optimal materno–fetal cholesterol transfer. These in utero epigenetics adaptations may also potentially trigger the long-term susceptibility of the newborn to dyslipidemia and CVD.